2001
DOI: 10.1016/s0092-8674(01)00328-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Organ, Multi-Lineage Engraftment by a Single Bone Marrow-Derived Stem Cell

Abstract: Purification of rare hematopoietic stem cell(s) (HSC) to homogeneity is required to study their self-renewal, differentiation, phenotype, and homing. Long-term repopulation (LTR) of irradiated hosts and serial transplantation to secondary hosts represent the gold standard for demonstrating self-renewal and differentiation, the defining properties of HSC. We show that rare cells that home to bone marrow can LTR primary and secondary recipients. During the homing, CD34 and SCA-1 expression increases uniquely on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,750
3
45

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,469 publications
(1,839 citation statements)
references
References 38 publications
41
1,750
3
45
Order By: Relevance
“…The self-renewal capacities of stromal keratocytes are poorly understood and the cell source is unclear so far. It is reported that BMderived stem cells, such as hematopoietic and mesenchymal stem cells, have tremendous differentiation capacity beyond their blastoderm (Gussoni et al, 1999;Krause et al, 2001;Jiang et al, 2002). Taken together, the present findings raise the possibility that the stem cells from the transplanted BM may transdifferentiate into corneal keratocytes and communicate with neighboring keratocytes, organizing themselves into a keratocyte cellular network in the corneal stroma.…”
Section: Discussionsupporting
confidence: 61%
“…The self-renewal capacities of stromal keratocytes are poorly understood and the cell source is unclear so far. It is reported that BMderived stem cells, such as hematopoietic and mesenchymal stem cells, have tremendous differentiation capacity beyond their blastoderm (Gussoni et al, 1999;Krause et al, 2001;Jiang et al, 2002). Taken together, the present findings raise the possibility that the stem cells from the transplanted BM may transdifferentiate into corneal keratocytes and communicate with neighboring keratocytes, organizing themselves into a keratocyte cellular network in the corneal stroma.…”
Section: Discussionsupporting
confidence: 61%
“…Immunohistochemistry staining was performed with specific antibodies against CD45, wheat germ agglutinin, α‐sarcomeric actin, BrdU , and IdU (Sigma). To assess the fate of the transplanted male CPCs, Y chromosome was detected by fluorescence in situ hybridization according to the modified manufacturer's protocol (ID Labs, London, ON) 3, 8, 13…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (MSCs) are currently among the best characterized adult stem cells (Majumdar et al, 1998;Pittenger et al, 1999) isolated from various tissue sources such as fat, muscle, and bone (Jiang et al, 2002b;Sottile et al, 2002;Zuk et al, 2002). These cells are able to differentiate into bone, fat, cartilage, muscle tissue, and neurons (Mackay et al, 1998;Reyes et al, 2001;Sekiya et al, 2004;Woodbury et al, 2000) and were ultimately reported in almost all cell lineages (Jiang et al, 2002;Krause et al, 2001). For these reasons, the isolation and manipulation of adult stem cells represents a promising tool for understanding tissue development and regeneration, as well as for studying the engineered repair of tissues and organs (Orlic et al, 2001;Pittenger and Martin, 2004;Wakitani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%